Evaluation of health data interoperability and governance policies to support program planning, monitoring and evaluation (M&E) - Suci Nur Qudsiyah; Riesvito Khairurizky; Muhammad Hafizh Azzuraiqi (PT WIM Solusi Prima, 2026)
The development of information technology has driven the utilization of Health Information Systems (HIS) as a foundation for transforming healthcare services, particularly in supporting evidence-based planning and program monitoring and evaluation (M&E). In Indonesia, the implementation of interoperability policies through the SATUSEHAT platform aims to integrate health data across healthcare facilities; however, it still faces challenges such as system fragmentation, differences in data standards, limited human resource capacity, and uneven connectivity among facilities. This study aims to evaluate interoperability policies and health data governance and their implications for planning and M&E of health programs. The method used is a systematic literature review, with data sources from Google Scholar, PubMed and ScienceDirect, using keywords related to interoperability, data governance, data quality, and program M&E, with inclusion criteria of publications from the last 5–10 years. The results show that interoperability depends not only on technical standards such as HL7-FHIR but also on strong data governance, integrated system architecture, and a supportive technological ecosystem. The implementation of open standards and API-based systems can improve data integration and quality; however, it remains suboptimal without policy harmonization and cross-sector collaboration. In conclusion, strengthening data governance, ensuring consistency in standards implementation, enhancing human resource capacity, and expanding SATUSEHAT integration are essential to produce accurate, integrated, and real-time data to support evidence-based decision-making.